Dr. Salim Rahimov — Deep Plane Facelift — Baku - Rahimov, Salim (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Salim Rahimov, practicing in Baku, Azerbaijan. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003261; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; azerbaijan; baku